Environmental control and waste disposal - Koch, B.A.; Allee, G.L.; Hines, Robert H. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A system for aerobic oxidation of waste has been used continuously since 1968 and is now functioning successfully. Figure 11.1 shows general design of the units. Originally "paddle wheels" were used to circulate liquid waste, keep solids in suspension, and mix oxygen into the liquid. Their performance, however, was less than desirable. Excessive foaming of liquid in the pits kept recurring, and maintenance of "paddle wheels" was expensive and time consuming.
Swine Industry Day 1974 is known as Swine Day, 1974
Keywords: Swine; Environmental control; Waste disposal